HAMBATAN KOMUNIKASI YANG SERING DIHADAPI DALAM SEBUAH ORGANISASI - Rismayanti, Rismayanti (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2018)
Organization is a collection of several people who have the same vision and idea. However, this does not mean that an organization can be carried out sustainably and harmoniously, there are many stumbling blocks when they run organization. Small or large organization does not guarantee the harmony of members in an organization. Through observation and literacy studies this writing contains some obstacles especially in the communication process in an organization. The causes often arise from internal organization such as disharmony between officials, selfishness, prioritizing group interests, which impact complicated problems and even can destroy the organization. If an organization has effective communication, it will be certain that every problem will be resolved properly. Effective communication is a way to make harmonis relationship in an organization, and then the goals can be achieved.